ANALISIS GENDER DALAM PELAKSANAAN MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) DI UNIVERSITAS MUHAMMADIYAH MAKASSAR - Hadisaputra; Ulviani, Maria; Tasman, Amrullah; Ardiansyah; Yewi , Delila (JURNAL SIPAKALEBBI, 2023)
This research aims to examine the implementation of the Independent Learning Campus (MBKM) policy with a focus on gender dynamics at Muhammadiyah University of Makassar. This study investigates how gender influences student participation and experiences in three main forms of MBKM programs: internship activities, independent entrepreneurship, and campus teaching. The method used is descriptive qualitative with a phenomenological approach. Data was collected through interviews, observation, and documentation. The data analysis stages include transcription, repeated reading of the data, data organization, categorization, and triangulation to ensure the validity of the data. The research results show that the implementation of MBKM has had a positive impact in increasing students’ adaptability to technological changes, improving hard and soft skills, and encouraging entrepreneurship; however, findings also indicate differences by gender that require further attention.